2019
DOI: 10.1093/cvr/cvz192
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal doxorubicin attenuates cardiotoxicity via induction of interferon-related DNA damage resistance

Abstract: Aims The clinical application of doxorubicin (DOX) is severely compromised by its cardiotoxic effects, which limit the therapeutic index and the cumulative dose. Liposomal encapsulation of DOX (Myocet®) provides a certain protective effect against cardiotoxicity by reducing myocardial drug accumulation. We aimed to evaluate transcriptomic responses to anthracyclines with different cardiotoxicity profiles in a translational large animal model for identifying potential alleviation strategies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 39 publications
1
63
0
Order By: Relevance
“…Doxorubicin (Dox) belongs to anthracyclines, one of the most frequently used chemotherapeutics for a wide range of malignancies, such as breast cancer and haematologic cancer 1 . However, the clinical application of Dox is limited by its lethal cardiomyopathy, which is characterized by decrease in left ventricular ejection fraction (LVEF) or even heart failure 1 , 2 , 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Doxorubicin (Dox) belongs to anthracyclines, one of the most frequently used chemotherapeutics for a wide range of malignancies, such as breast cancer and haematologic cancer 1 . However, the clinical application of Dox is limited by its lethal cardiomyopathy, which is characterized by decrease in left ventricular ejection fraction (LVEF) or even heart failure 1 , 2 , 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have reported pro brotic effects of anthracyclines, cyclophosphamide, paclitaxel and trastuzumab in the myocardium of experimental models of cardiotoxicity [8][9][10][11][12][13][14], and in rodent cardiac broblasts [9,11], the role of these agents in HCFs has not been characterized. In this regard, we describe that doxorubicin, cyclophosphamide and trastuzumab stimulated the differentiation to a myo broblast collagen-synthesizing phenotype, including enhanced presence of PICP in the extracellular medium.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, cardiotoxicity due to breast cancer treatment, particularly anthracycline-based cancer chemotherapy (ACC), has been attributed to cardiomyocyte damage and death, with amino-terminal pro-brain natriuretic peptide (NT-proBNP) and high-sensitivity troponins (hs-Tn) as the most commonly used biomarkers to detect cardiac damage in these patients [5,6]. However, it has been suggested that myocardial interstitial brosis (MIF) is an additional important mechanism contributing to left ventricular dysfunction (LVD) and adverse clinical evolution in ACC-treated patients [6,7], as well as in patients treated with other oncologic drugs such as cyclophosphamide, taxane agents and anti-HER2 therapies [8][9][10][11][12][13][14]. As cumulative evidence suggest that the detrimental impact of MIF on LV function is related to both an excess in collagen type-I ber cross-linking and deposition [15], these characteristics of the collagen ber should be evaluated in the myocardium of patients receiving ACC.…”
Section: Introductionmentioning
confidence: 99%
“…Left ventricular dysfunction and heart failure (HF), which are typically described as cardiotoxicity, are the most concerning cardiovascular complications of anticancer chemotherapies, which cause an increase in morbidity and mortality (1). Based on previous studies of anthracycline cardiotoxicity, increasing attention has focused on tyrosine kinase inhibitors (TKIs), a type of pharmaceutical drug inhibiting tyrosine kinases by competitively binding to and inhibiting their ATP binding pocket (2)(3)(4)(5). TKIs are characterized by being multi-targeted anticancer agents that lack sufficient specificity, which markedly increases the risk of cardiotoxicity (5).…”
Section: Introductionmentioning
confidence: 99%